NF-κB and its crosstalk with endoplasmic reticulum stress in atherosclerosis - Li, Wenjing; Jin, Kehan; Luo, Jichang; Xu, Wenlong; Wu, Yujie; Zhou, Jia; Wang, Yilin; Xu, Ran; Jiao, Liqun; Wang, Tao; Yang, Ge (Frontiers in Cardiovascular Medicine, 2022)
Atherosclerosis (AS) is a common cardiovascular disease with complex pathogenesis, in which multiple pathways and their interweaving regulatory mechanism remain unclear. The primary transcription factor NF-κB plays a critical role in AS via modulating the expression of a series of inflammatory mediators under various stimuli such as cytokines, microbial antigens, and intracellular stresses. Endoplasmic reticulum (ER) stress, caused by the disrupted synthesis and secretion of protein, links inflammation, metabolic signals, and other cellular processes via the unfolded protein response (UPR). Both NF-κB and ER stress share the intersection regarding their molecular regulation and function and are regarded as critical individual contributors to AS. In this review, we summarize the multiple interactions between NF-κB and ER stress activation, including the UPR, NLRP3 inflammasome, and reactive oxygen species (ROS) generation, which have been ignored in the pathogenesis of AS. Given the multiple links between NF-κB and ER stress, we speculate that the integrated network contributes to the understanding of molecular mechanisms of AS. This review aims to provide an insight into these interactions and their underlying roles in the progression of AS, highlighting potential pharmacological targets against the atherosclerotic inflammatory process.